2019
DOI: 10.1177/1087054719859074
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variability–Based Functional Brain Lateralization Study in ADHD

Abstract: Objective: The aim of this work is to explore the relationship between temporal variability and brain lateralization in ADHD. Method: The temporal variabilities of 116 brain regions based on resting-state functional magnetic resonance imaging (rs-fMRI) data were calculated for analysis. Results: Between-group comparison revealed that in comparison with the controls, ADHD participants showed significantly higher temporal variability in the left superior frontal gyrus (medial), left rectus gyrus, left inferior p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Some aspects of brain asymmetry are partly heritable (Guadalupe et al, 2016;Kong et al, 2018), so that future gene mapping studies for brain asymmetry and disorder susceptibility may help to resolve causal relations underlying their associations. One functional imaging study (94 cases, 85 controls) reported lower rightward lateralization in medial orbitofrontal cortex in ADHD compared to controls, based on temporal variability during resting-state (Zou & Yang, 2019). Furthermore, a study of 218 participants with ADHD and 358 healthy controls reported that orbitofrontal cortex thickness, but not surface area, showed a left > right asymmetry in childhood controls that switched to right > left asymmetry by late adolescence, while this change did not occur to the same extent in ADHD (Shaw et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some aspects of brain asymmetry are partly heritable (Guadalupe et al, 2016;Kong et al, 2018), so that future gene mapping studies for brain asymmetry and disorder susceptibility may help to resolve causal relations underlying their associations. One functional imaging study (94 cases, 85 controls) reported lower rightward lateralization in medial orbitofrontal cortex in ADHD compared to controls, based on temporal variability during resting-state (Zou & Yang, 2019). Furthermore, a study of 218 participants with ADHD and 358 healthy controls reported that orbitofrontal cortex thickness, but not surface area, showed a left > right asymmetry in childhood controls that switched to right > left asymmetry by late adolescence, while this change did not occur to the same extent in ADHD (Shaw et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, various neuropsychological and functional imaging studies have found differences between people with ADHD compared to controls (e.g., (Cortese et al, 2012)), with some pointing to a particular involvement of right hemisphere alterations (Geeraerts, Lafosse, Vaes, Vandenbussche, & Verfaillie, 2008;Hale et al,2010Hale et al, , 2014Langleben et al, 2001;Stefanatos & Wasserstein, 2001;Vance et al, 2007). However, not all functional data fit a primarily right-hemisphere model (Hale et al, 2009;Mohamed, Börger, Geuze, & van der Meere, 2016;Zou & Yang, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Some aspects of brain asymmetry are partly heritable (30,38), so that future gene mapping studies for brain asymmetry and disorder susceptibility may help to resolve causal relations underlying their associations. One functional imaging study (94 cases, 85 controls) reported lower rightward lateralization in medial orbitofrontal cortex in ADHD compared to controls, based on temporal variability during resting-state (21). Furthermore, a study of 218 participants with ADHD and 358 healthy controls reported that orbitofrontal cortex thickness, but not surface area, showed a left>right asymmetry in childhood controls that switched to right>left asymmetry by late adolescence, while this change did not occur to the same extent in ADHD (51).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, various neuropsychological and functional imaging studies have found lateralized differences between people with ADHD compared to controls (e.g., (9)(10)(11)(12)(13)(14)), with some pointing to a particular involvement of right hemisphere alterations (15)(16)(17)(18)(19)(20). However, not all functional data fit a primarily righthemisphere model (21). In terms of brain anatomy, several studies have reported altered asymmetry of the caudate nucleus in ADHD, although not consistently in the direction of effect (9,10,(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…We next used iSECA to perform genetic overlap analyses 53 with our mvGWAS results in relation to GWAS summary statistics from neurodevelopmental disorders, behavioral and psychological traits which have been reported to associate phenotypically with aspects of structural and/or functional brain asymmetry: attention deficit hyperactivity disorder [54][55][56][57][58] , autism spectrum disorder [59][60][61][62][63][64] , educational attainment 42,65,66 , handedness 4,22,67 , intelligence 43,[68][69][70][71] and schizophrenia [72][73][74][75][76][77] . There was evidence for genetic overlap between brain asymmetries and autism (p=0.005), educational attainment (p=0.001) and schizophrenia (p=0.002) which remained significant at Bonferroni-corrected P<0.05 ( Fig.…”
mentioning
confidence: 99%